2020
DOI: 10.13057/biodiv/d210558
|View full text |Cite
|
Sign up to set email alerts
|

The combination of mare's milk and grape polyphenol extract for treatment of dysbiosis induced by dextran sulfate sodium

Abstract: Abstract. Kozhakhmetov S, Babenko D, Nurgaziyev M, Tuyakova A, Nurgozhina A, Muhanbetganov N, Chulenbayeva L, Sergazy S, Gulyayev A, Saliev T, Kushugulova A. 2020. The combination of mare's milk and grape polyphenol extract for treatment of dysbiosis induced by dextran sulfate sodium. Biodiversitas 21: 2275-2280. This study showed the potential of a biological product based on mare's milk and a complex of grape polyphenols to modulate intestinal microflora after dextran sulfate sodium  (DSS)-induced dysbiosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The current findings of the beneficial effects of mare's milk on the intestinal microbiota are supported by previously published studies that showed a significant association between mare's milk and the actions of intestinal microflora [ 23 ]. Interestingly, animal treatment with SP alone for 7 days restored the microflora levels of Lactobacillus population to that of the HC group, which shows that SP has much broader activity in restoring a wider range of microbiota than the positive control 5-ASA.…”
Section: Discussionsupporting
confidence: 85%
“…The current findings of the beneficial effects of mare's milk on the intestinal microbiota are supported by previously published studies that showed a significant association between mare's milk and the actions of intestinal microflora [ 23 ]. Interestingly, animal treatment with SP alone for 7 days restored the microflora levels of Lactobacillus population to that of the HC group, which shows that SP has much broader activity in restoring a wider range of microbiota than the positive control 5-ASA.…”
Section: Discussionsupporting
confidence: 85%
“…Considering the role of the gut–liver axis in the development of liver fibrosis and the importance of gut microbiota homeostasis [ [29] , [30] , [31] ], we speculate that lingonberry; cranberry and blueberry extracts may achieve their anti-fibrotic activity by improving and maintaining the integrity of intestinal epithelial, and gut microbiota. Previously, we showed that plant polyphenols can significantly influence and change intestinal microbiota [ 32 ]. Nevertheless, further research is needed to decipher the exact protective mechanism of blueberry and cranberry extracts against CCl4-induced liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…They prefer oligosaccharides to be consumed and have immunomodulatory effects (Ding et al 2017;Kusharyati et al 2020). Mare's milk also contains biologically active compounds; lysozyme; lactoferrin; the vitamins A, B1, B2, B6, B9, B12, and C; and the trace elements Na, Ca, K, P, Fe, Mg, Cu, I, S, Si, Zn, and C (Kozhakhmetov et al 2020).…”
Section: Introductionmentioning
confidence: 99%